Reclassification of Acute Myeloid Leukemia According to the 2016 WHO Classification - Jung, Jin; Cho, Byung-Sik; Kim, Hee-Je; Han, Eunhee; Jang, Woori; Han, Kyungja; Lee, Jae-Wook; Chung, Nack-Gyun; Cho, Bin; Kim, Myungshin; Kim, Yonggoo (Annals of laboratory medicine, 2019)
We reviewed our leukemia database to reclassify 610 patients previously diagnosed as having acute myeloid leukemia (AML) according to the updated 2016 WHO classification. Nine patients were categorized as having myelodysplastic syndrome and myeloid neoplasms with germline predisposition. AML with recurrent genetic abnormalities accounted for 57.4% (345/601) of the patients under the 2016 WHO classification. AML with mutated was the most common form (16.5%), with the majority associated with monocytic differentiation (63.6%). AML with double mutations accounted for 8.3% of these cases, and the majority were previously diagnosed as AML with/without maturation (78.0%). These newly classified mutations were mutually exclusive without overlapping with other forms of AML with recurrent genetic abnormalities. AML with mutated and AML with myelodysplasia-related changes comprised the oldest patients, whereas AML with included the youngest patients. The leukocyte count was highest in AML with mutated , and the percentage of peripheral blood blasts was the highest in AML with double mutations. Our results indicate that implementation of the 2016 WHO classification of AML would not pose major difficulties in clinical practice. Hematopathologists should review and prepare genetic tests for the new classification, according to their clinical laboratory conditions.